الأمير خالد وتوجهاته السياسية من خلال جريدة الأقدام 1919 - 1923 - غمام علي، إبراهيم, نعرورة، رضا (جامعة الوادي university of Eloued, 2021)
الملخص: ظهرت العدٌد من الشخصٌات الجزائرٌة التً لعبت أدوارا بارزة فً مقاومة االستعمار الفرنسً، خاصة فً مطلع القرن العشرٌن مستخدمة مختلف الوسائل المتاحة، ومن بٌن هذه الشخصٌات األمٌر خالد الهاشمً الذي ساهم بشكل كبٌر وف ّعال فً تبلور الحركة الوطنٌة الجزائرٌة، حٌث انطلق فً النضال السٌاسً بمساندته لحركة الشبان الجزائرٌٌن، ثم و ّجه رسالة للرئٌس األمرٌكً وٌلسون أثناء انعقاد مؤتمر الصلح، مطالبا بحق الجزائرٌٌن فً تقرٌر مصٌرهم، كما خاض معترك االنتخابات البلدٌة والنٌابٌة وتصدى للمستوطنٌن واالندماجٌٌن وحلفائهم من بعض الجزائرٌٌن، من خالل فضح سٌاستهم على صفحات جرٌدة االقدام، التً اتخذها كمرآة تعكس مختلف مطالبه وتوجهاته السٌاسٌة خاصة خالل الفترة بٌن سنتً 9191 و9191 ،وقد واجه األمٌر خالد بسبب ذلك تحالفا قوٌا من غالة المستوطنٌن وحلفائهم من الجزائرٌٌن، مما أدى إلى نفٌه سنة 9191. ]2[ Summary: Many Algerian personalities who played prominent roles in resisting French colonialism appeared, Especially at the beginning of the twentieth century, using the various available means. Among these figures is Prince Khaled Al Hashemi, who contributed significantly and effectively to the crystallization of the Algerian national movement, Where he launched into the political struggle by supporting the movement of the Algerian youth, and then sent a message to American President Wilson during the convening of the Peace Conference, demanding the right of Algerians to self-determination, He also participated in the municipal and parliamentary elections and confronted the settlers, the integrationists and their allies from some Algerians, Where he exposed their policy on the pages of Al-Aqdam newspaper, which he took as a mirror that reflects his various demands and political orientations, especially during the period between 1919 and 1923, Because of this, Prince Khaled faced a strong alliance of the extremist settlers and their Algerian allies, which led to his exile in 1923
مذكرة ماستر تاريخ تخصص تاريخ المغرب العربي المعاصر
Keywords: الأمير خالد; Prince Khaled; Prince Khaled